Wheat Water Ecophysiology: A Review on Recent Developments - Batool, Asfa; Irum, Momena; Gui, Yan-Wen; Zhu, Shuang-Guo; Zhao, Ling; Xiong, You-Cai (Global Journal Of Botanical Science, 2023)
With exceptional tolerance to a wide range of climatic circumstances, from temperate to desert, and from warm to cold regions; wheat (Triticum aestivum L.) is an important food crop on a worldwide scale. This flexibility is linked to the crop's highly flexible DNA (Deoxyribonucleic acid), which is complicated in nature. The impacts of climate change and other stresses on wheat ecophysiology and productivity remain topics of concern despite our very thorough knowledge of wheat physiology, growth, and development. This study emphasizes the implementation of new information in breeding and crop management techniques while concentrating especially on the ecophysiology of water usage in wheat plants. The focus is on comprehending physiological processes at the level of the whole plant and organ, giving breeders and agronomist insightful information. Where necessary to explain physiological responses seen at higher organizational levels, cellular-level explanations are presented. Various topics, including wheat physiology, ecological interactions, and yield determination, are covered in this review that emphasizes recent developments in our knowledge of yield production. The knowledge gathered from this study may be used to help build crop production systems that maximize yield potential. Additionally, this study offers physiological and ecological methods for creating wheat production systems that are high-yielding, resource-efficient, and quality-focused. Although there is a wealth of information on wheat physiology that directly aids agronomists and breeders, more research is needed to fully grasp yield under stress. However, using already available physiological information provides encouraging potential for further development. The review prioritizes yield and yield-forming processes because they have the biggest potential impact on global wheat production, even though other factors like lodging resistance, growth regulator application, weed competition, soil mechanical impedance, and nutrient imbalances are not covered.